2012
DOI: 10.1126/science.1217141
|View full text |Cite
|
Sign up to set email alerts
|

GBP5 Promotes NLRP3 Inflammasome Assembly and Immunity in Mammals

Abstract: Inflammasomes are sensory complexes that alert the immune system to the presence of infection or tissue damage. These complexes assemble NLR (nucleotide binding and oligomerization, leucine-rich repeat) or ALR (absent in melanoma 2-like receptor) proteins to activate caspase-1 cleavage and interleukin (IL)-1β/IL-18 secretion. Here, we identified a non-NLR/ALR human protein that stimulates inflammasome assembly: guanylate binding protein 5 (GBP5). GBP5 promoted selective NLRP3 inflammasome responses to pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
518
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(544 citation statements)
references
References 39 publications
25
518
1
Order By: Relevance
“…Similar to the current model for Mx proteins and the mitochondrial Drp1, such polymers of hGBP1 could serve as protein depots, ensuring a kind of buffer function for the rapid mobilization of the protein in immune response (46)(47)(48). Alternatively, such polymers could function as a scaffold for the assembly of other large immune-related complexes such as the inflammasome (5,49,50). At this point, we do not have data to judge the relative amounts of hGBP1 assembled in polymers or residing at membrane surfaces.…”
Section: Discussionmentioning
confidence: 89%
“…Similar to the current model for Mx proteins and the mitochondrial Drp1, such polymers of hGBP1 could serve as protein depots, ensuring a kind of buffer function for the rapid mobilization of the protein in immune response (46)(47)(48). Alternatively, such polymers could function as a scaffold for the assembly of other large immune-related complexes such as the inflammasome (5,49,50). At this point, we do not have data to judge the relative amounts of hGBP1 assembled in polymers or residing at membrane surfaces.…”
Section: Discussionmentioning
confidence: 89%
“…34,35 The functions of other GBPs are less clear although animal and in-vitro models suggest a protective role in controlling infection and autoimmunity as GBPs are essential for formation of the inflammasome complex. 36 The inflammasome complex promotes inflammatory cell death through activation of cysteine protease caspase-1 and is purported to have tumor suppressive effects in some studies. 37 Our finding of upregulated GBP1, GBP4, and GBP5 in medullary carcinoma compared with all other colorectal carcinomas including microsatellite unstable colorectal carcinomas suggests a possible mechanistic link between the pro-inflammatory microenvironment and observed more favorable clinical outcomes in microsatellite unstable colorectal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…106 It has also been shown that guanylate-binding protein (GBP) 5, a member of the interferon-inducible GBP family, binds to the pyrin domain of NLRP3 and serves as an activator of selected NLRP3 inflammasomes, especially in response to soluble agents or Salmonella typhimurium, but not crystalline agents or double-stranded DNA. 111 Recently, HOIL-1L, a component of linear ubiquitination assembly complex (LUBAC), was found to be an essential activator of NLRP3/ASC inflammasome assembly through linear ubiquitination of ASC, a novel LUBAC substrate. 112 Additionally, the direct binding of NLRP3 to the mitochondrial lipid cardiolipin is important for NLRP3 inflammasome activation in response to both ROSdependent and -independent activators.…”
Section: Adaptors/molecules Involved In Activation Of the Nlrp3 Inflamentioning
confidence: 99%